PENILAIAN POTENSI ODTW DI OBJEK WISATA ALAM PANTAI PASIR MAYANG DI DESA PAMPANG HARAPAN KECAMATAN SUKADANA KABUPATEN KAYONG UTARA - Aini, Misturatul; Rifanjani, Slamet; Siahaan, Sarma (JURNAL HUTAN LESTARI, 2019)
Pasir Mayang beach in Pampang village, Sukadana sub-district, Kayong Utara regency, West Kalimantan Barat, has its own appeal, the of research was mayang is also decorated with large stones that add to its attraction. purpose this to know the potential of natural tourism attraction of the pasir mayang beach. The study was conducted using survey methods with interview/questionnaire techniques. Sampling/respondents were conducted accidentally and purposively. The results of research revealed that the potential and attraction of Pasir Mayang beach judget according to criteria of assessment are tourism attraction, conditions of socio-economic, accessibility, accommodation, infrastructure and supporting facilities as well as the availability of clean water. Total value of assessment natural tourism attraction potency is about 2419,1 with in average them of 403,18. Category of this value are potential to develop.Keywords: Accidental Sampling, Pasir Mayang Beach, Tourism Object Potency.